2022
DOI: 10.15869/itobiad.937383
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Analysis of the Relationship Between Internal Migration, Education, and Growth in Turkey

Abstract: Bu makale, en az iki hakem tarafından incelenmiş ve intihal içermediği, araştırma ve yayın etiğine uyulduğu teyit edilmiştir. / This article has been reviewed by at least two referees and it has been confirmed that it is plagiarism-free and complies with research and publication ethics. http://www.itobiad.com/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Studies on international population mobility in Turkey [15,49,50] primarily focused on the effect of inter-regional mobility on economic growth. İçduygu et al [15] examined the relationship between socio-economic development and international migration at the district level and observed that people from regions with low socio-economic development immigrate more, and these regions are relatively more impoverished.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies on international population mobility in Turkey [15,49,50] primarily focused on the effect of inter-regional mobility on economic growth. İçduygu et al [15] examined the relationship between socio-economic development and international migration at the district level and observed that people from regions with low socio-economic development immigrate more, and these regions are relatively more impoverished.…”
Section: Literature Reviewmentioning
confidence: 99%